Endovascular Revascularization as a Treatment Option for Peripheral Arterial Disease due to Diabetes in Saudi Arabia: Public Awareness Survey - Afnan Hammad Ali Alshammari; Noura Hamad Rasheed Alshurtan; Amirah Fahad Mohammed Alshammeri; Abdulaziz Ayied Abdullah Alharbi (The Arab Journal of Interventional Radiology, 2021)
Objectives Diabetic foot disease is a common and serious complication of diabetes that represents a major global health concern with high mortality and morbidity rates. Successful revascularization and improved perfusion have had fundamental roles in reducing the rate of amputation in diabetic foot patients over the last decade. Creating public awareness plays a key role in early treatment and prevention of amputation. The aim of this study was to determine if people are aware of endovascular revascularization as a therapeutic option for diabetes-related peripheral artery disease. Methods The study is a community-based observational descriptive cross-sectional study that was conducted to assess Saudi population knowledge and awareness about endovascular revascularization as a treatment option of diabetic foot disease through interventional radiology. The self-administered online survey was randomly distributed with a maximum of 20 multiple choice questions through social media channels. Results Endovascular revascularization as a treatment of diabetes-related peripheral artery disease through interventional radiology was unknown to 90.2% of the participants. Awareness has been influenced by many factors including age, occupation, and family history. Conclusion This study highlights the importance of raising public awareness about endovascular revascularization as a treatment option for diabetes-related peripheral arterial disease in suitable patients.